ADDITIONAL OF CHEMICAL ENHANCER FOR INCREASING THE PENETRATIONAL FLUORIDE MOUSE SKIN: PENAMBAHAN BAHAN KIMIA UNTUK PENINGKATAN DAYA TEMBUS ION FLUORIDA PADA KULIT TIKUS - Diyah Fatmasari; Iwan Dwi Prahasto; Akhmad Kharis Nugroho; Widjijono (Dentika: Dental Journal, 2012)
Fluoride plays an important roles in reducing dental caries by improving remineralization process and strengthening emailthrough forming fluoroapatite which is more resistant to acid. Fluoride systemic mode without passing metabolism withsmall and controlled dose need to be developed such as Transdermal route. The aims of this research was to find iffluoride solution with and without enhancer solution is able to penetrate to skin. Quasy experimental design with post testonly control group design as research approach was used. Transport test with Franz Like Diffusion cell used as theinstrument in vitro skin permeation test with hairless and full thickness mouse skin as membrane between donor andrecipient cell. Two groups of donor cell was fluoride solution and fluoride added with chemical enhancer: oleic acid andiso propyl alcohol (IPA) solution and recipient solution was CMF PBS 0,1 M pH 7,4. Control group was oleic acidsolution. Sample was taken for time interval of 4, 20 and 24 hours and Fluoride containt was measured by PotensiometerSpesific Ion Fluoride. The results showed that there was an influence of transport test both on NaF solution andNaF+oleat acid and IPA solution (p= 0.00) and (0.00) on fluoride permeation, however there was no significant differenceon control group (p= 0.07). NaF added with chemical enhancer solution and it had higher penetrating power than othersolution. It can be concluded that added chemical enhancer can increase the penetration of fluoride.